2010
DOI: 10.1111/j.1420-9101.2010.02099.x
|View full text |Cite
|
Sign up to set email alerts
|

Enantiomorphs differ in shape in opposite directions between populations

Abstract: Development is left–right reversed between dextral and sinistral morphs of snails. In sympatry, they share the same gene pool, including polygenes for shell shape. Nevertheless, their shell shapes are not the mirror images of each other. This triggered a debate between hypotheses that argue either for a developmental constraint or for zygotic pleiotropic effects of the polarity gene. We found that dextrals can be wider or narrower than sinistrals depending on the population, contrary to the prediction of invar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 43 publications
0
17
0
Order By: Relevance
“…[29]. Furthermore, the difference in external shell shape between wild-type and mutants also gets flipped in those species [50]. We expect the chiral sense of the large-scale flow to depend on universal properties of non-muscle myosin II, and hence not to flip its sign from species to species.…”
Section: Questions About This Theory and Experimental Testsmentioning
confidence: 95%
See 1 more Smart Citation
“…[29]. Furthermore, the difference in external shell shape between wild-type and mutants also gets flipped in those species [50]. We expect the chiral sense of the large-scale flow to depend on universal properties of non-muscle myosin II, and hence not to flip its sign from species to species.…”
Section: Questions About This Theory and Experimental Testsmentioning
confidence: 95%
“…There is one qualification: as handedness is propagated from its original cause, either from lower to higher levels in these mechanisms of the origin, or from upstream to downstream in the signaling cascades that specify every cell's fate in development, the response in the reversed organism probably does become functionally symmetry-reversed at some point. In snails, though, the external shell shape is subtly different between the mutants and wild type [50]; of course, this may be one of the many independent effects expected from a mutation affecting the cytoskeleton.…”
Section: Questions About This Theory and Experimental Testsmentioning
confidence: 99%
“…Such differences have been found for snail shells in species with dimorphism due to sinistral and dextral coiling [111][112][113][114] as well as for the "left-sided" and "right-sided" forms of the European flounder [183].…”
Section: Antisymmetrymentioning
confidence: 99%
“…More recently, dozens of studies in a wide range of different animal taxa have found statistically significant directional asymmetry of shape [13,16,. Even in snails where morphs with opposite directions of shell coiling occur within populations, a subtle directional pattern of asymmetry is superimposed on the dimorphism, because the average shell shapes of the two morphs are not precise mirror images of each other [111][112][113][114]. Therefore, just as conspicuous directional asymmetry of internal organs is near-ubiquitous among bilaterian animals, it seems that, for a wide range of animals, even structures that seem superficially symmetric show a subtle directional asymmetry of shape.…”
Section: Directional Asymmetrymentioning
confidence: 99%
“…In the Polynesian tree snail Partula suturalis Pfeiffer, which is extinct in the wild (Murray et al 1998), the dominant sinistral allele or linked genes widen the shell by zygotic expression regardless of the polarity phenotype (Johnson 1987) and maybe by maternal expression (Davison et al 2009a). Also in the Southeast Asian tree snail genus Amphidromus (Sutcharit et al 2006), shell shapes of enantiomorphs differ within populations (Nakadera et al 2010; Schilthuizen and Haase 2010). Variability among populations in the direction of interchiral difference in A. atricallosus (Gould) indicates the presence of genetic variation in the pleiotropic effects of the polarity or linked genes on shape, which suggests epistasis between the polarity and other nuclear genes (Nakadera et al 2010).…”
mentioning
confidence: 99%